PENGUNGKAPAN LINGKUNGAN PERUSAHAAN: DITINJAU DARI MANAJEMEN LABA DAN MEKANISME TATA KELOLA PERUSAHAAN YANG BAIK - Kurnia Rahmadani; Edfan Darlis; Pipin Kurnia (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2021)
The objective of this study is to analyze the influence of earnings management and good corporate governance mechanisms towards corporate environmental disclosure (CED). Good corporate governace mechanisms are measured by the proportion of independent board, the number of audit committee meetings and the size of audit committee. Earnings management is measured by the modified discreationary accrual Jones model. The population of this study is mining, plantation and manufacturing companies listed in Indonesian Stock Exchange (IDX) in 2015-2017 . The sample of this study was selected with a purposive sampling concept. The company has 5 mining companies, 12 plantation companies and 65 manufacturing companies companies that meet the criteria. Hypothesis testing is carried out using panel data regression method, with a statistical test tool used, namely Eviews 10.The results of this study indicate that the proportion of independent board have a significant effect on the disclosure of corporate environmental on the level significant 0,05, the number of audit committee meetings have a significant effect on the disclosure of corporate environmental on the level significant 0,00 and the size of audit committee have a significant effect on the disclosure of corporate environmental on the level significant 0,03 in Indonesian mining, plantation and manufacturing companies. Meanwhile, earnings management do not affect the disclosure of corporate environmental have a significant effect on the disclosure of corporate environmental on the level significant 0,92 in Indonesian mining, plantation and manufacturing companies.